Factors Associated to Cancer Related Fatigue: A Literature Review - Nurhesti, Putu Oka Yuli; Yudari, Made Adi; Lasiani, Ni Luh; Lisnawati, Luh Gede; Mariani, Nyoman (Journal of A Sustainable Global South; Vol 4 No 2 (2020): August 2020, 2020)
Cancer related fatigue is one of the common problems that occur in patients with cancer. This condition is also experienced by cancer patients who receive chemotherapy, radiation therapy, bone marrow transplantation, or other cancer treatments. Continued of cancer related fatigue can disturb the quality of life of patients so that a good assessment and management of this condition is needed. The purpose of this study is for factors related to fatigue in cancer patients. These factors can be new scientific evidence for the treatment of fatigue in cancer patients. This was literature review study. Research data is collected from books, research results, journals, magazines and articles related to the research objectives. The results show that various factors associated to cancer related fatigue discussed in patients are hemoglobin level, type and amount of therapy, sleep quality, nutritional status, level of physical activity, psychological pressure, stress, infection status and comorbidities. Therapy on fatigue patients can be done by overcoming the causal factors. Index Terms — cancer, cancer related fatigue, factors associated